Association of blood pressure with brain perfusion and structure: A population-based prospective study - Li, Xiaoshuai; Hui, Ying; Shi, Huijing; Zhao, Xinyu; Li, Rui; Chen, Qian; Lv, Han; Li, Jing; Chen, Shuohua; Zhao, Pengfei; Wu, Yuntao; Wu, Shouling; et al. (European journal of radiology, 2023)
•Elevated DBP was associated with decreases in total and regional brain perfusion.•Higher SBP and DBP were associated with decreased total and regional brain volume.•Higher SBP and PP were associated with increased WMH burden.•The association of BP and perfusion was not affected by decreased brain volume. To explore the association of blood pressure (BP) measurements with cerebral blood flow (CBF) and brain structure in general population. This prospective study included 902 participants from Kailuan community. All participants underwent brain MRI and BP measurements. The association of BP indicators with CBF, brain tissue volume and white matter hyperintensity (WMH) volume were investigated. In addition, mediation analysis was used to determine whether significantly changed brain tissue volume explained associations between BP and CBF. Elevated diastolic BP (DBP), but not systolic BP (SBP), was associated with lower CBF in the total brain (β [95 % CI]: −0.62 [−1.14, −0.10]), total gray matter (β [95 % CI]: −0.71 [−1.27, −0.14]), hippocampus (β [95 % CI]: −0.59 [−1.13, −0.05]), frontal (β [95 % CI]: −0.72 [−1.31, −0.13]), parietal (β [95 % CI]: −0.92 [−1.54, −0.3]), temporal (β [95 % CI]: −0.63 [−1.18, −0.08]), and occipital lobe (β [95 % CI]: −0.69 [−1.37, −0.01]). Higher SBP and DBP were associated with reduced total and regional brain tissue volume (all p < 0.05). Increased SBP and PP were associated with higher total and periventricular WMH volume (all p < 0.05). In addition, mediation analysis identified that significantly decreased brain volume did not mediate the associations of BP measurements and lower CBF in corresponding region (all p > 0.05). Elevated BP level was associated with decreased total and regional CBF and brain tissue volume and increased WMH burden.